Another Strategy for the Treatment of Thyroglossal Duct Cyst: Totally Endoscopic Surgery by Breast Approach. Issue 2 (April 2018) - Qu, Rui; Wang, Cunchuan; Dong, Zhiyong; Li, Jinyi; Liu, Daosheng
Abstract : Objective: Open surgery is the most common treatment of thyroglossal duct cyst (TGDC), but it leaves obvious neck scarring. This study aimed to explore the feasibility and strategy of total endoscopic procedure by breast approach to avoid such scarring on the neck. Materials and Methods: This study reviewed 13 patients who underwent endoscopic resection of TGDC and 15 patients who underwent open resection of TGDC. We compared and analyzed factors including operative time, estimated blood loss, postoperative hospitalization, complications, and cosmetic effect. Results: The surgery by the endoscopic approach was successfully completed in 13 cases and no one was converted to an open procedure. Another 15 cases were successfully performed by an open procedure. There were no significant differences between the 2 procedures in the mean cyst size, drainage time, intraoperative blood loss, and postoperative hospital stay. The cosmetic effect was better and the operative time was longer in the endoscopic approach. Two cases had swallowing discomfort after surgery in the endoscopic approach, whereas one case developed this complication in the open approach. On patient treated with each approach developed infection. One patient developed skin bruise and one patient developed subcutaneous hydros in the endoscopic approach, whereas no complications developed in the open approach. There were no incidences of uncontrolled bleeding, tracheal injury, dysphagia, salivary fistula, or asphyxia/dyspnea in both approaches, nor were there any deaths or recurrences of TGDC during the follow-up period. Conclusion: With strict indications, the total endoscopic breast procedure is feasible and effective for selected patients. This procedure can be another choice for patients who wish to avoid neck scarring when undergoing treatment for TGDC. Abstract : Supplemental Digital Content is available in the text.